A comparative evaluation of electrical velocimetry and inert gas rebreathing for the non-invasive assessment of cardiac output - Trinkmann, Frederik; Berger, Manuel; Hoffmann, Ursula; Borggrefe, Martin; Kaden, Jens; Saur, Joachim (Clinical research in cardiology, 2011)
When assessing the function of the cardiovascular system, cardiac output (CO) is a substantial parameter. For its determination, numerous non-invasive techniques have been proposed in the recent years including inert gas rebreathing (IGR) and impedance cardiography (ICG). The aim of our study was to evaluate whether a novel ICG algorithm (electrical velocimetry) and IGR can be used interchangeably in the clinical setting.
Gesehen am 16.11.2022